The making of China's foreign policy in the 21st century historical sources, institutions/players, and perceptions of power relations - Zhao, Suisheng 1954- (Routledge, Taylor & Francis Group, 2016)
"This book is a study of the making of foreign policy of China, a rising power in the 21st century. It examines three sets of driving forces behind China's foreign policy making. One is historical sources, including the selective memories and reconstruction of the glorious empire with an ethnocentric world outlook and the century of humiliation at the hands of foreign imperialist powers. The second set is domestic institutions and players, particularly the proliferation of new party and government institutions and players, such as the national security commission, foreign policy think tanks, media and local governments. The third set is Chinese perception of power relations, particularly their position in the international system and their position relations with major powers. This book consists of articles from the Journal of Contemporary China"--Publisher's description.